Optimising concrete containing palm oil clinker and palm oil fuel ash using response surface method - Hussein M., Hamada; Alyaa A., Al-Attar; Bassam, Tayeh; Fadzil, Mat Yahaya; Yazan I., Abu Aisheh (Ain Shams University, 2023)
Cement production led to the consumption of high energy and generated harmful gases, such as CO2. Therefore, the use of alternative materials becomes necessary. The research attempts to use palm oil clinker (POC) and ultrafine palm oil fuel ash (UPOFA) as a full replacement of coarse aggregate and partial cement replacement, respectively. This study aims to use the response surface method (RSM) to optimise the properties of concrete, namely, density and water absorption. The study investigated the density and water absorption of concrete using RSM. Results showed that the density reduced sharply owing to the full replacement coarse aggregate by POC aggregate. Meanwhile, water absorption increased significantly due to the rise in the POC aggregate replacement. However, water absorption decreased because of the use of UPOFA as cement replacement. The study recommended the use of more UPOFA as cement replacement because of its high pozzolanic property.